2022
DOI: 10.11591/ijere.v11i4.23207
|View full text |Cite
|
Sign up to set email alerts
|

Employability of technology and livelihood education graduates

Abstract: <span lang="EN-US">This paper examines the job-seeking experiences of the 2019 Bachelor of Technology and Livelihood Education (BTLE) graduates from a teacher education university. Identifying these graduates’ employability is vital to the field of educational research, particularly in determining the impact of a higher education institution’s BTLE program. Employing quantitative research design through a survey of 50 graduates, this research revealed that great majority of them have been employed, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Employment Status: The study's findings on alumni employment status align with previous research on graduates' employability. Similar tracer studies conducted at Caraga State University (Monzon et al, 2022) and focusing on technology and livelihood education graduates (Cacho et al, 2022) have reported a diverse range of employment statuses among alumni. It is a reflection of the dynamic and multifaceted nature of the job market, where graduates pursue various pathways, including further education or part-time/freelance work.…”
Section: Results and Findingssupporting
confidence: 64%
See 1 more Smart Citation
“…Employment Status: The study's findings on alumni employment status align with previous research on graduates' employability. Similar tracer studies conducted at Caraga State University (Monzon et al, 2022) and focusing on technology and livelihood education graduates (Cacho et al, 2022) have reported a diverse range of employment statuses among alumni. It is a reflection of the dynamic and multifaceted nature of the job market, where graduates pursue various pathways, including further education or part-time/freelance work.…”
Section: Results and Findingssupporting
confidence: 64%
“…1. Employment Status: The alumni's employment status varied, with some employed, others pursuing further education, and a few experiencing unemployment (Monzon et al, 2022;Cacho et al, 2022). During an informal interview with "Al-part 23," a recent graduate from the College of Arts and Sciences major in Psychology, she shared her journey to secure employment: "After graduation, I faced a brief period of unemployment, but I kept networking and honing my skills.…”
Section: Thematic Analysismentioning
confidence: 99%
“…The study conducted by Arsad et al [52] confirmed a lack of 87% practical gap among Nigerian graduates. The quality of an educational institution can be measured by its output in terms of employability and entrepreneurship [62]- [65]. This is synonymous with the assertions that teaching in Nigerian higher Institutions is generally theoretical and does not translate to employability [66], [67].…”
Section: Resultsmentioning
confidence: 99%
“…According to the study conducted by Coward [87], non-technical skills are a better predictor of success than technical skills even though, not all soft skills are important for a particular discipline. Similarly, Cacho et al [62] showed that the lack of soft skills is responsible for the massive unemployment among Nigerian University graduates. Therefore, the combination of electrical-specific skills and electrical mindset skills will be very useful in engendering a purposeful entrepreneurship skills framework for the employability of the students of electrical technology in the changing world of work.…”
Section: "They Are Technicians They Must Be Able To Detect Faults And...mentioning
confidence: 96%
“…Employability abilities are generic skills, attitudes, and behaviors employer's demand [17]. However, academic, personal management, and teamwork skills were included [18]- [21].…”
Section: Literature Reviewmentioning
confidence: 99%